Standardization of oral food challenges as a method for diagnosis of food allergy in children of the Russian Federation: study protocol and preliminary results - D. M. Levina; S. O. Lukyanova; N. V. Zinovieva; Ju. V. Petrova; M. A. Rumyantsev; S. A. Konchina; E. I. Iakovleva; A. B. Chashchukhina; A. I. Kolotilina; I. A. Korsunskiy; D. B. Munblit; I. I. Afukov; et al. (Лечащий Врач)
Background. Food allergy is a serious, life-threatening condition that negatively impacts the quality of life of patients and their families, especially among children. In Europe, approximately 7 million people suffer from food allergy, while in Russia, the prevalence varies from 5% to 30%. Accurate diagnosis and treatment of food allergy are crucial to preventing complications and improving quality of life. Primary diagnostic methods include medical history, laboratory tests, and elimination diets, though each has its limitations. Globally, oral food challenges are considered the "gold standard" for food allergy diagnosis. It helps to establish a precise connection between the allergen and the reaction, reducing anxiety for patients and their families.Objective. To evaluate the feasibility of using oral food challenges as a diagnostic method for food allergies in children.Materials and methods. This single-center, prospective, interventional, non-randomized, uncontrolled study is being conducted from January 1, 2022, to December 31, 2024, at the G. N. Speransky Children’s Hospital No. 9 in Moscow. Children aged 6 months to 17 years, suspected of having an immediate allergic reaction to cow's milk protein and/or egg protein by a doctor or legal guardian, were invited to participate. The study involves using an open food challenge for diagnosing food allergies. An open food challenge involves consuming increasing amounts of the suspected allergen (milk, egg, etc.) in its natural form under medical supervision. To determine the necessity of a provocation test, a consultation is conducted, including a physical examination, medical history, and allergy testing (specific IgE blood tests, component diagnostics for milk and egg, and a prick test with the native allergen). Additionally, during the consultation, questionnaires on anxiety and quality of life were completed. Our patient selection and test procedure algorithm is an adapted version of existing protocols from international allergology organizations.Conclusions. Preliminary results indicate that the provocation test is a safe diagnostic method when following a strict patient selection and test procedure algorithm. Notably, parents of children undergoing these tests exhibit high anxiety levels. We plan to continue this study and assess personal and situational anxiety levels over time post oral food challenges.